Optimization of pyrolysis of oil palm empty fruit bunches - Sukiran, M.A.; Bakar, N.K.A.; Chin, C.M. (2009)
In this study, pyrolysis of oil palm empty fruit bunches (EFB) was investigated using a quartz fluidizedfixed bed reactor. The effects of various pyrolysis temperatures, particle sizes and heating rates on the yields of the products were investigated. The temperature of pyrolysis and heating rate were varied in the range of 300°C-700°C and 10°C-100°C min1, respectively. The particle size was varied in the range of<90, 91-106, 107-125 and 126-250 μm. The products obtained from pyrolysis of EFB were bio-oil, char and gas. Under the experimental conditions, the maximum bio-oil yield was 42 obtained at 500°C, with a heating rate of 100°C min 1 and a particle size of 91-1 06 μm. The maximum yield of char was 42, obtained at a pyrolysis temperature of 300°C, heating rate of 30°C min1 and particle size of 91-106 μm. Meanwhile, the optimum yield of gas was 46, which could be achieved at a pyrolysis temperature of 700°C, heating rate of3O°C min1 and particle size of 107-125 μm.